"I Know What Them Girls Like": A Rhetorical Analysis of Thug Appeal in Rap Lyrics. (January 2016) - Craig, Richard T.
Rap music, once associated with low-income urban communities, has become a staple in contemporary pop culture extending globally beyond the ghettos, and projects from where it began. Along with the transcendence of the art, those who master the art are repositioning themselves in a social context. This analysis observed the content of rap lyrics to understand how the genre depicts the rappers' regards toward and relationships with women they know intimately, particularly content that portrays these young men as "thugs." This observation explores the characteristics put forth by the rapper, specifically those demonstrating thug characteristics, as a potential dating and mating partner for young women. This analysis takes into consideration psychological concepts offering knowledge into peoples' perceived and real reasons for establishing relationships. Psychological theories contribute to the analysis of the observed actions and principles found in the content of the reviewed lyrics. At the core of this study are concepts of Black male masculinity and intimate relationships. This study analyzed rap lyrics to understand how the "thug" is presented to the female audience.